Belongingness in medical students: did it change during lockdown? - Rob Daniels; Eric Buramba; Kato Denis (Medical Education Online, 2024)
Belongingness has been proposed as a potential proxy for legitimate peripheral participation in medical education. Previous studies have shown good internal and external validity for tools designed to measure this variable, with potential use measuring the effectiveness of clinical teaching environments and as a marker of student wellbeing. This study examined changes in belongingness in medical students at the University of Exeter measured in spring 2019 and the equivalent period in 2021, during which COVID-19 related restrictions were in place in the United Kingdom. This study used a validated assessment tool that was self-administered via an online survey platform in 2021. Anonymised data was collected from undergraduate medical students from all years of training and results compared with previous data collected in 2019. The belongingness assessment tool described here had validity in undergraduate medical students studying at the University of Exeter and identified statistically significant changes in belongingness (as measured with this tool) between 2019 and the period during which COVID-19 restrictions were in place. These results suggest that belongingness – in undergraduate medical students fluctuates and varies under different conditions and that there was a statistically significant change during the period of lockdown restrictions. The ability to measure this key facet of educational development has the potential to monitor teaching environments to ensure optimal learning conditions for all students. Further work is required to assess whether the impacts of lockdown restrictions are transient or persist beyond the period of teaching restrictions and to determine any association with academic outcomes.